Detonation properties of ammonium nitrate/nitramine-based composite propellants. Issue 3 (3rd July 2019) - Kohga, Makoto; Shigi, Daisuke; Beppu, Masuhiro
ABSTRACT: Ammonium nitrate (AN) propellants have attracted attention because of their low cost and ecofriendliness despite certain major disadvantages such as low burning rate, poor ignitability, low energy, and volume change due to phase transition of AN. The addition of nitramine to AN propellants is one of the approaches to overcome these disadvantages. However, AN/nitramine propellants are characterized by easy initiation, high sensitivity, and high detonation velocity because of the high energy of nitramine. The detonation properties of AN/nitramine propellants were investigated in this study. It was observed that the AN/nitramine propellant required a booster to detonate the propellants, as detonation did not occur while using only a commercial electric blasting cap. It was further observed that the detonation velocity ( D ) increased linearly as the mass of nitramine per unit propellant volume was increased, and AN had a negligible effect on the detonation properties. An approximate equation was derived from the relationship between D and the mass per unit propellant volume of nitramine. The dominant factors that can be used to estimate the detonation/no-detonation boundaries of the propellants were identified, and the experimental boundary equations were determined using these factors.